Effects of embryo characteristics in frozen-thawed single euploid blastocyst transfers on pregnancy outcomes: a retrospective cohort study - Özer, Gönül; Özkara, Gülçin (The European Research Journal, 2023)
Objectives: Our study examined the effects of the trophectoderm biopsy (TB) day and the presence of necrotic foci (NF) or separate blastomeres (SB) within euploid embryos on in vitro fertilization (IVF) pregnancy outcomes. Methods: This retrospective cohort study was conducted from January 2017 to September 2021 at Memorial Sisli Hospital, Istanbul, Turkey. The study comprised a total of 2758 frozen-thawed euploid embryo transfer cycles. After thawing, blastocysts were graded using Gardner’s classification Top-Quality (TQ), Good-Quality (GQ), Moderate-Quality (MQ), Poor-Quality (PQ) and further divided into groups according to the presence of NF and/or SB and evaluated for pregnancy outcomes. Results: There were significant correlations between pregnancy outcomes and the degree of blastocoele expansion, as well as the presence of NF or SB in the euploid embryo. Ongoing pregnancy rates were lower in the group with NF in the inner cell mass (ICM) or trophectoderm (TE) than in the group without NF. The presence of SB decreased the rates of ongoing pregnancy and increased the rates of miscarriage. Embryos with expansion grades ≤ 3 had lower rates of ongoing pregnancy and higher rates of miscarriage compared to embryos with expansion grades> 3. TQ and GQ embryos had a higher rate of ongoing pregnancy and a lower rate of miscarriage than MQ and PQ embryos. Conclusions: When selecting the embryo to be transferred to a patient, careful consideration should be given to the morphological grade of the embryo as well as whether or not it contains NF and SB.